Affect, Cognition and Stereotyping : Interactive Processes in Group Perception. - Mackie, Diane M. (Elsevier Science, 1993)
This volume presents a collection of chapters exploring the interface of cognitive and affective processes in stereotyping. Stereotypes and prejudice have long been topics of interest in social psychology, but early literature and research in this area focused on affect alone, while later studies focused primarily on cognitive factors associated with information processing strategies. This volume integrates the roles of both affect and cognition with regard to the formation, representation, and modification of stereotypes and the implications of these processes for the escalation or ameliorati.